2008
DOI: 10.1051/agro:2008020
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of plant strips for sustainable mountain agriculture

Abstract: -Erosion degrades soil quality in agricultural ecosystems, thereby reducing the productivity of the land. Semi-natural vegetation and diverse cropping systems have been converted into monocultures with low tree densities, leaving the soil unprotected. We evaluated the association in soil-and water-conservation systems with production in traditional almond orchards and the beneficial impact of plant strips in mountainous agriculture. Soil loss, runoff and nutrient loss over a four-year period (2002)(2003)(2004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Tillage in the row middles is common for some perennial crops, such as almonds, olives, citrus, and grapevines [11,67], and is generally performed to remove weeds to avoid water and nutrient competition, resulting in bare soil between tree rows [68,69]. Adopting no-tillage in combination with cover crops has been identified as a reliable management practice in tree cropping systems [70,71] that increases soil C sequestration and reduces N fertilization inputs compared with conventional tillage (down to a depth of 15-20 cm), primarily due to the beneficial effects on soil microbial diversity [11,14,18,23]. For example, intercropping olive (O. europea) with grasses increased bacterial diversity in no-tillage systems compared with conventional treatments, and changes in microbial diversity were positively correlated with improved olive yield [49].…”
Section: Cover Crops Increase Soil Microbial Diversitymentioning
confidence: 99%
“…Tillage in the row middles is common for some perennial crops, such as almonds, olives, citrus, and grapevines [11,67], and is generally performed to remove weeds to avoid water and nutrient competition, resulting in bare soil between tree rows [68,69]. Adopting no-tillage in combination with cover crops has been identified as a reliable management practice in tree cropping systems [70,71] that increases soil C sequestration and reduces N fertilization inputs compared with conventional tillage (down to a depth of 15-20 cm), primarily due to the beneficial effects on soil microbial diversity [11,14,18,23]. For example, intercropping olive (O. europea) with grasses increased bacterial diversity in no-tillage systems compared with conventional treatments, and changes in microbial diversity were positively correlated with improved olive yield [49].…”
Section: Cover Crops Increase Soil Microbial Diversitymentioning
confidence: 99%
“…It is well known that trees grown with an intensive weed control give rise to higher erosion rates than no-till agricultural production; however, this problem may be controlled by planting cover crops between the tree rows, as demonstrated in cultivating rainfed-tree crops (Durán et al 2008). Moreover, Malik et al (2001) studied the effects of varying strip widths of four species of cover crops on the growth of sweet gum (Liquidambar styraciflua L.) seedlings planted as a short-rotation bioenergy woody crop.…”
Section: Environmental Impact and Challenges For Sustainable Energy Fmentioning
confidence: 99%
“…Over shorter time scales of up to decades or centuries, plot-scale studies provide important insights into the mechanisms through which vegetation cover affects erosion processes and denudation rates. These studies have shown that both the type and density of vegetation cover increase the resistance of soil to erosion through the binding effects of roots, the formation of soil aggregates, the resistance to flow exerted by leaf litter and stems, and the protection of the surface from rainsplash (e.g., Dunne et al, 1978Dunne et al, , 2010Wainwright et al, 2000;Gyssels and Poesen, 2003;Durán Zuazo et al, 2008). Higher infiltration rates in densely vegetated areas with thick soils also decrease the likelihood of overland flow, which can rapidly denude slopes (Horton, 1933(Horton, , 1945Abrahams et al, 1995;Prosser and Dietrich, 1995).…”
Section: Introductionmentioning
confidence: 99%